Molecularly Imprinted Polymer-Based Luminescent Chemosensors - Ruoyang Liu; Chi-Chiu Ko (Biosensors, 2023)
Molecularly imprinted polymer (MIP)-based luminescent chemosensors combine the advantages of the highly specific molecular recognition of the imprinting sites and the high sensitivity with the luminescence detection. These advantages have drawn great attention during the past two decades. Luminescent molecularly imprinted polymers (luminescent MIPs) towards different targeted analytes are constructed with different strategies, such as the incorporation of luminescent functional monomers, physical entrapment, covalent attachment of luminescent signaling elements on the MIPs, and surface-imprinting polymerization on the luminescent nanomaterials. In this review, we will discuss the design strategies and sensing approaches of luminescent MIP-based chemosensors, as well as their selected applications in biosensing, bioimaging, food safety, and clinical diagnosis. The limitations and prospects for the future development of MIP-based luminescent chemosensors will also be discussed.